2020
DOI: 10.1042/bsr20200049
|View full text |Cite
|
Sign up to set email alerts
|

The construction and analysis of tumor-infiltrating immune cells and ceRNA networks in metastatic adrenal cortical carcinoma

Abstract: Purpose: To construct and analyze tumor-infiltrating immune cell and ceRNA (competitive endogenous RNA) networks in metastatic adrenal cortical carcinoma (ACC). Methods: A ceRNA network was established to identify the ceRNAs involved in metastasis of ACC based on 92 samples from TCGA, including 18 cases of metastasis and 74 cases of non-metastatic primary tumors. And the algorithm "cell type identification by estimating relative subsets of RNA transcripts (CIBERSORT)" was used to quantify the proportion of imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Many studies also have shown that CD8+ T cells usually mean a better prognosis among cancer patients [44,45]. M0 macrophages were reported to be inversely associated with patients' outcomes in various, such as adrenal cortical carcinoma and lung cancer [46,47]. Nowadays, majority studies evaluated the degree of smoking based on the frequency of tobacco use to define heavy smokers and light smokers without uniform quantifying standards [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies also have shown that CD8+ T cells usually mean a better prognosis among cancer patients [44,45]. M0 macrophages were reported to be inversely associated with patients' outcomes in various, such as adrenal cortical carcinoma and lung cancer [46,47]. Nowadays, majority studies evaluated the degree of smoking based on the frequency of tobacco use to define heavy smokers and light smokers without uniform quantifying standards [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…However, the intrinsic heterogeneity of tumor often engenders homogeneous cancer subtypes possessing distinct molecular features and therapeutic responses, which could invalidate most of the biomarkers from previous studies. Emerging studies have incorporated tumor heterogeneity in ceRNA network analyses 46,47 but works considering key driver mutations were scarce. Interestingly, the DEGs identi ed in patients separated by TP53 mutational status were enriched in similar pathways, denoting that the effect conferred by TP53 anomaly should be investigated in a more microcosmic way, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…M0 macrophages can polarize into M1 and M2 macrophages in different environments, and evidence accumulated from many cancer models demonstrated that M1 macrophages possess inflammation-promoting characteristics, which activate cytotoxic anti-tumor mechanisms ( 25 ). According to Huang et al., the degree of M0 macrophage infiltration was significantly higher in metastatic ACC than in non-metastatic patients ( 26 ). Notably, the immune risk may lead to the suppression of M1 macrophage infiltration and the promotion of M0 infiltration, which suggests that high immune risk may contribute to tumor immune escape and poor prognosis in patients with ACC.…”
Section: Discussionmentioning
confidence: 99%